The Effect of Service Quality, Company Image and Trust on Customer Satisfaction of Muamalat Bank - Anggoro, Tommy; Karyatun, Subur; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to address the existing research gap by investigating the impact of service quality, company image, and trust on customer satisfaction at Bank Muamalat Fatmawati branch, South Jakarta. The sample comprises 100 respondents who are customers of the mentioned branch. Primary data was collected through the distribution of questionnaires, and the data analysis utilized inferential analysis, employing multiple linear regression via the Statistical Product and Service Solution (SPSS) version 23.0 program. The results of the multiple linear regression analysis reveal that the service quality variable has a positive and significant influence on customer satisfaction at Bank Muamalat Fatmawati branch, South Jakarta. Similarly, the corporate image variable exhibits a positive and significant impact on customer satisfaction at the same branch. Additionally, the variable of trust demonstrates a positive and significant influence on customer satisfaction at Bank Muamalat Fatmawati branch, South Jakarta.